Gestão de Empresas Familiares - MACEDO, Beatriz Dias de; ATANAZIO, Daniela da Silva; SOUZA, Jaci Maria de; MARTIN, Rayara Souza; SANTOS, Thainá Cruz dos (166, 2016)
O presente trabalho tem a finalidade de demonstrar o funcionamento da gestão administrativa de uma empresa familiar. Serão abordados os principais temas que iremos discutir no decorrer do trabalho como: estrutura empresarial, a empresa familiar e o processo sucessório. De acordo com a pesquisa do Sebrae 90% das empresas são familiares e nisso está em evidência que nos dias de hoje é possível abrir um negócio em família.

Family businesses are made up of members of the same family and usually have two or more generations present in their management. These firms are of great importance in economics, society and politics and represent the majority in all countries (BERNHORET, R, 2011). The present work has the finality of demonstrating the operation of administrative management of a family business. The main topics will be discussed during the course of the work will be discussed such as: business structure, family business and succession process. According Sebrae's research, 90% of the companies are familiar and it is evident that it is now possible to start a family business.
Keywords: Empresas familiares; Administração; Gestão e Negócios